Development of juice extraction process for pomegranate (Punica granatum): Evaluation and physicochemical aspects - JITHENDER, BHUKYA; VYAS, D M; C, NICKHIL; RATHOD, P J (The Indian Journal of Agricultural Sciences, 2021)
The pomegranate (Punica granatum L.) consumption is tremendously increasing due to the development of diversified value-added products and its health benefit among all age groups of consumers. The initial stage in extracting the pomegranate fruit juice is a very drudgery and time-consuming process. To meet these difficulties, the pomegranate juice extractor was developed consisting of feed chute, carrier roller, crushing roller and juice collecting platform with filter. The performance evaluation of the developed juice extractor resulted 357 kg/h of machine capacity, 88% of extraction efficiency and 12% of extraction losses. The quantitative analysis after juice extraction showed enhanced results in pH (3.32), TSS (19.13) total phenol (0.209 %) and the total flavonoids content (22.2 mg CE/100 mL).